(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2017)
Physiological and biochemical characteristics of nine different tomato cultivars were studied in order to select which of the cultivar has the overall best quality. The tomato cultivars (Lalima, Manik, Summer, Deshy, Anupama, Jhumka, Chaity, Bizly and Lovely) were collected from different places of Rajshahi region. Those cultivars showed variability in physiological and biochemical characteristics. The range for the tomato quality parameters are as follows: fruit weight (44.76-111.70g), juice (81.25-69.94%), dry matter (7.58-9.92%), moisture content (90.08-92.42%), ash (0.438-0.530%), acidity (0.083-0.129% as citric acid), ?-carotene (298-380µg/100g), vitamin C (6.98-11.43 mg/100g ), total sugar (3.45-4.52%), reducing sugar (1.21-1.56%), non reducing sugar (2.24-2.97%), protein (0.525-0.654%), iron (0.152-0.215 mg/100g), phosphorous (21.94-28.31 mg/100g), calcium (38.15-42.31 mg/100g), carbohydrate (4.18-6.24%), starch (0.16-0.21%), and so on. Bizli tomato cultivar has the best overall qualities with respect to fruit colour, fruit size, fruit pulp taste. These data of quality characteristics of tomato provide important information for consumers, producers and industrial processor for plantation and processing industry. Bangladesh J. Sci. Ind. Res. 52(3), 195-200, 2017